Shifts in nursing and medical students' attitudes, beliefs and behaviours about interprofessional work: An interprofessional placement in ambulatory care. Issue 15 (21st June 2018) - Seaman, Karla; Saunders, Rosemary; Dugmore, Helen; Tobin, Claire; Singer, Rachel; Lake, Fiona
Abstract : Aim and objectives: To examine students' beliefs, behaviours and attitudes in relation to interprofessional socialisation, and their expectations and experience, before and after a 2‐week clinical placement in ambulatory care. Background: Interprofessional clinical placements for students are important for developing an understanding of interprofessional collaboration and identity, for the benefit of patient care. Ambulatory care environment involves collaborative management of complex chronic problems. This educator supported placement that enabled final‐year nursing and medical students to work together. Design: A descriptive matched before‐after study was conducted. Methods: Students' completed an online questionnaire before and after their clinical placement. The questionnaire comprised of three sections: demographic information, the Interprofessional Socialisation and Valuing Scale and open‐ended questions. Descriptive analysis and paired t ‐tests were conducted for the three subscales, and thematic analysis of qualitative responses was conducted. Results: Sixty‐two of the 151 students between 2011–2014 completed both surveys. There was a significant increase after placement in the overall Interprofessional Socialisation and Valuing Scale scores. The change was greater for nursing students compared with medical students, although for both groups the change was small. The majority had a good‐to‐very good experience learning each other's and their own professions and identified the nurse educator and teaching registrar as key to success. Conclusion: A clinical placement in an ambulatory setting for nursing and medical students resulted in an increase in self‐perceived ability to work with others and in valuing working with others. Relevance to clinical practice: Interprofessional clinical placements are essential for students to understand interprofessional practice for better patient outcomes and developing their own perspective of future work within an interprofessional team. Ambulatory care is an ideal environment for nursing and other health professional students to engage in interprofessional clinical placements.